2013
DOI: 10.1021/bm4011408
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Conformation and Interaction of Gene Delivery Vector Polyethylenimine with Phospholipid Bilayer at Different Protonation State

Abstract: Polyethylenimine (PEI) is a pH sensitive polymer possessing stretched and coiled conformation at low and high pH, respectively. It is an efficient gene delivery agent. Thus, the interaction of PEI with the biomembrane is very crucial to understand the gene delivery mechanism. In this report, we have investigated the structural properties of PEI and bilayer due to the interaction of PEI with lipid molecules. PEI has coil structure at high pH while at low pH it is elongated. The neutral PEI chain predominately s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 50 publications
5
42
0
Order By: Relevance
“…Endosomal leakiness can be a result of small defects that arise in the endosomal membrane when pressure builds up upon osmotic swelling in combination with interaction of the protonated PEI chains with the endosomal lipid biliayer. 55 Co-incubation of PEI polyplexes with quenched calcein confirmed this hypothesis since both HeLa and ARPE-19 cells that had taken up PEI/pDNA polyplexes showed cytosolic calcein release in virtually every cell whereas calcein remained trapped in endosomes in the absence of polyplexes (Fig. 7).…”
Section: Endosomal Leakinesssupporting
confidence: 54%
“…Endosomal leakiness can be a result of small defects that arise in the endosomal membrane when pressure builds up upon osmotic swelling in combination with interaction of the protonated PEI chains with the endosomal lipid biliayer. 55 Co-incubation of PEI polyplexes with quenched calcein confirmed this hypothesis since both HeLa and ARPE-19 cells that had taken up PEI/pDNA polyplexes showed cytosolic calcein release in virtually every cell whereas calcein remained trapped in endosomes in the absence of polyplexes (Fig. 7).…”
Section: Endosomal Leakinesssupporting
confidence: 54%
“…Simulations showed that individual cationic oligomers can bind the lipid bilayer surface, driven by the electrostatic interactions with the lipid phosphate groups. Occasionally an oligomer inserted more deeply in the membrane, as observed for PEI [92], without destabilizing membrane structure. Simultaneous interaction of two oligomers, instead, led to the formation water pores.…”
Section: Linear Polyelectrolitesmentioning
confidence: 89%
“…Its protonation state is controlled simply by pH, and the protonated form (low pH) is known to be cytotoxic [91]. Choudhury et al studied the interaction of linear PEI with zwitterionic (POPC) membranes using atomistic MD simulations [92]. In simulations, both the protonated form (extended) and the unprotonated form (compact) interacted stably with the membrane surface, without affecting membrane structural properties.…”
Section: Linear Polyelectrolitesmentioning
confidence: 99%
“…The mechanism by which polymers modify and interact with lipid bilayers is a crucial step for the development of new polymer-based drug nano-carriers. [1][2][3][4] Such nanocarriers can be developed entirely from polymers (polymersomes, micelles, dendrimers), 5 or, to minimize the side effects, be self-assembled from a mixture of polymers and lipids (hybrid particles). The latter type of vesicles should have the advantage of retaining the good mechanical properties typical of the polymer vesicles and of displaying milder adverse effects.…”
Section: Introductionmentioning
confidence: 99%